Efektifitas “Plasma” Schoology dalam Meningkatkan Self Regulated Learning (SRL) Siswa Kelas XII IPA SMAN 1 Gedongtataan - Aswin Saputra (Lembaga Pengembangan Kinerja Dosen, 2025)
The use of virtual classrooms in the learning process is a strategic step to create a flexible learning experience, accessible anytime and anywhere. Schoology's